(untitled) (Revista de Estudios Europeos, 2026)
This paper addresses the conflict between the finality of national administrative acts and the effective application of European Union law, which arises when such acts contradict a subsequent interpretation by the Court of Justice, all from the perspective of the principle of equality among European citizens. It is argued that subordinating the review to the various domestic legal systems leads to material inequalities in the exercise of community rights. Based on the doctrine established in the landmark Kühne & Heitz ruling, the paper advocates for the establishment of common minimum conditions for the review of administrative acts, to ensure full and non-discriminatory legal integration within the European Union, in line with the European integration process.